2021
DOI: 10.3390/economies9020054
|View full text |Cite
|
Sign up to set email alerts
|

The Intra-EU Value Chain: An Approach to Its Economic Dimension and Environmental Impact

Abstract: This paper aims to analyze the economic dimension and environmental impact of intra-EU value-added generation linked to global value chains (GVCs) through input-output analysis. For this purpose, information has been collected from TiVA (Trade in Value Added, OECD) and Eora databases for the years 2005 and 2015. From an economic perspective, the results point to a strengthening of the value-added generated within Factory Europe. From an environmental perspective, all EU28 members have reduced their exports-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…According to this theory, countries are polluting at the early stages of their economic development while their preferences for environmental quality increase when reaching a threshold of income per capita. Many studies found empirical evidence of the environmental Kuznets curve hypothesis in developed countries (Blampied, 2020;Rodil-Marzábal & Campos-Romero, 2021) as well as in developing countries (Amowine et al, 2019;Tachega et al, 2021).…”
Section: Environmental Energy Efficiency In Africamentioning
confidence: 99%
“…According to this theory, countries are polluting at the early stages of their economic development while their preferences for environmental quality increase when reaching a threshold of income per capita. Many studies found empirical evidence of the environmental Kuznets curve hypothesis in developed countries (Blampied, 2020;Rodil-Marzábal & Campos-Romero, 2021) as well as in developing countries (Amowine et al, 2019;Tachega et al, 2021).…”
Section: Environmental Energy Efficiency In Africamentioning
confidence: 99%
“…Carbon dioxide emissions from China–Brazil trade had maintained a steady growth, and China was a net carbon dioxide emitter [ 11 ]. European economies with lower development levels (many Eastern and Southern countries) seemed to be still on the rising trend of carbon emission, while the more developed ones seemed to be on the decreasing trend of carbon emission between 2005 and 2015 [ 12 ]. Chinese scholars constructed a spatial correlation network of net carbon transfer in global trade including 185 countries (regions) in 2000 and 2015 and used multi-dimensional network measurement indicators to comprehensively examine the characteristics of change of the global trade embodied carbon emission network and the role and functional characteristics of the network sectors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%